Vegetable Oil based Bio-lubricants and Transformer Fluids Applications in Power Plants - Gnanasekaran, Dhorali (Materials Forming, Machining and Tribology,, 2018)
This book is discusses vegetable oil based biolubricants and their applications in the power distribution industry. Vegetable oil based lubricants offer significant advantages over petroleum-based lubricants, including biodegradability, cost-effectiveness, renewability, and lower environmental effects. This book provides a detailed literature survey of modified vegetable oils. It discusses the physical and chemical properties of vegetable oil, and their effects on its applications in tribology. The book discusses additives and enhancements to make vegetable oils suitable for use as lubricating oils and transformer oils in power plants and power distribution grids. The contents of the book will be useful to researchers and professionals as well as policy makers and standards agencies. .